Intelligence and Global Transportation Supply Chain Management: The Case of Oil and Gas Supply in the Gulf of Guinea - Nte, Ngboawaji Daniel (Maritime Park: Journal of Maritime Technology and Society, 2026)
The Gulf of Guinea (GoG) is a critical artery for global oil and gas distribution, yet its supply chain is plagued by a complex risk ecosystem. This study investigates the imperative of intelligence management in mitigating these risks. Employing a mixed-methods approach, it integrates quantitative data from the International Maritime Bureau (IMB) and MDAT-GoG (2020-2024) with qualitative insights from focused group interviews with 12 security and industry experts. The findings reveal an evolution in maritime criminality towards armed robbery and theft, persistent infrastructure deficits that act as risk multipliers, and a critical "intelligence deficit" hindering proactive risk management. The study concludes that security threats, infrastructural decay, and geopolitical instability are interconnected. It recommends regional intelligence collaboration via the Yaoundé Architecture, route optimization using digital tools, massive infrastructural investment, and a sustainable regional security framework to secure the oil and gas supply chain.